2006
DOI: 10.1159/000091539
|View full text |Cite
|
Sign up to set email alerts
|

Early Ischemic Edema on Cerebral Computed Tomography: Its Relation to Diffusion Changes and Hypoperfusion within 6 h after Human Ischemic Stroke

Abstract: Background: Brain tissue hypoattenuation on early computed tomography is frequently included in decision making in acute stroke management. However, its pathophysiological counterpart needs further evaluation. Methods: By comparative imaging with diffusion-weighted imaging and 15O-water positron emission tomography we aimed to interpret early (<6 h) hypoattenuation. Results: In 11 patients, the hypoattenuation corresponded to a decreased proton diffusion (median 115.9% relative DWI value) measured b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Hypoattenuation seen on NCCT correlates with severe hypoperfusion and decreased proton diffusion representing irreversible ischemic injury. 23,28 NCCT hypoattenuation is due to extra-to intracellular shift of brain tissue water, whereas hypoattenuation of CTA-SI most likely reflects reduction in blood and, therefore, contrast distribution to the affected territory. 9 Several earlier studies have suggested that CTA-SI are volume-weighted.…”
Section: Discussionmentioning
confidence: 99%
“…Hypoattenuation seen on NCCT correlates with severe hypoperfusion and decreased proton diffusion representing irreversible ischemic injury. 23,28 NCCT hypoattenuation is due to extra-to intracellular shift of brain tissue water, whereas hypoattenuation of CTA-SI most likely reflects reduction in blood and, therefore, contrast distribution to the affected territory. 9 Several earlier studies have suggested that CTA-SI are volume-weighted.…”
Section: Discussionmentioning
confidence: 99%
“…[25][26][27] Early ischemic changes are difficult to detect on NCCT, with low interobserver agreement for presence and extent. 29,30 Whereas loss of gray-white differentiation is consistent with infarction, 31 cerebral swelling may be intermixed, extending the apparent boundary of infarct. Cerebral swelling is associated with a variable and lower stroke risk 32 and may account for overestimation of initial infarct size on NCCT.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study using single-photon emission CT, the time from onset to CT and residual cerebral blood flow were independent factors that contributed to the presence of ECTs [16]. Another study using positron emission tomography also shows that ECTs reflect the coupling of the severity of ischemia [17]. These findings suggest that the earlier the manifestation of ECTs, the severer the depth of brain ischemia.…”
Section: Discussionmentioning
confidence: 99%